Migration Shipibo-conibo and sociocultural adaptation in Community New San Juan, Pucallpa-Ucayali, 2007-2014 - Díaz Encinas, Alida Díaz Encinas (2017)
The investigation «Migration Shipibo-conibo and sociocultural adaptation in the community of Nuevo San Juan, Pucallpa - Ucayali, 2007-2014» led us to the in-depth analysis of the sociocultural adaptation as a result of the migration phenomenon in the Shipibo-conibo population of the region, who face problems in their place of origin, which lead them to migrate to a location closer to the urban area. In this context, this migrant population, is subjected to a process of sociocultural adaptation, as part of the adaptation to the way of life in the place of destination and thus bring about a new social status with the aim of improving their expectations of life, translated into work improvements for adults and education for their children.